2021
DOI: 10.1021/acs.oprd.1c00117
|View full text |Cite
|
Sign up to set email alerts
|

On-Demand Continuous Manufacturing of Ciprofloxacin in Portable Plug-and-Play Factories: Implementation and In Situ Control of Downstream Production

Abstract: Traditional pharmaceutical manufacturing operates around a supply chain that is subject to complex logistics and is vulnerable to spikes in demand and interruptions. In this context, continuous pharmaceutical manufacturing in portable, refrigerator-sized factories is a promising solution with applications in battlefield medicine, pandemic response, and mitigation of local medical emergencies. A new iteration of the pharmacy on demand initiative is hereby presented, involving the development of equipment and pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 27 publications
0
24
0
Order By: Relevance
“…However, this can be achieved by final-product purification using techniques such as multicolumn chromatography catch-and-release chromatography, simulated moving bed (SMB), crystallisation, recrystallisation and centrifugal partition chromatography (CPC). 51,54–59 Adding to scalability concerns of some of these purification methodologies, these techniques have their drawbacks; crystallization and recrystallisation usually requires semi-batch processing, catch-and-release chromatography needs automated multiple columns switching and the SMB chromatography operation is technically complex and it uses expensive absorbents. 12,51,60 The application of various downstream continuous flow processing strategies examples are reviewed herein.…”
Section: Continuous-flow Downstream Processingmentioning
confidence: 99%
See 3 more Smart Citations
“…However, this can be achieved by final-product purification using techniques such as multicolumn chromatography catch-and-release chromatography, simulated moving bed (SMB), crystallisation, recrystallisation and centrifugal partition chromatography (CPC). 51,54–59 Adding to scalability concerns of some of these purification methodologies, these techniques have their drawbacks; crystallization and recrystallisation usually requires semi-batch processing, catch-and-release chromatography needs automated multiple columns switching and the SMB chromatography operation is technically complex and it uses expensive absorbents. 12,51,60 The application of various downstream continuous flow processing strategies examples are reviewed herein.…”
Section: Continuous-flow Downstream Processingmentioning
confidence: 99%
“…Capellades et al 58 demonstrated the implementation and in situ control of downstream production of ciprofloxacin in portable plug-and-play continuous flow platform. The work mainly focused on the implementation and in situ feedback control strategies for downstream manufacturing (Fig.…”
Section: Continuous-flow Downstream Processingmentioning
confidence: 99%
See 2 more Smart Citations
“…Various multistep continuous flow synthetic procedures for active pharmaceutical ingredients (APIs) have been reported. [31][32][33][34][35][36][37][38][39] Herein, we take advantage of continuous flow chemistry technology to develop isocyanate free, rapid and efficient synthetic approaches towards glipizide 1 a and glibenclamide 1 b from commercially available chemicals. Due to the similarities in the chemical structures of the two drugs, a similar general synthetic approach can be used.…”
Section: Introductionmentioning
confidence: 99%